THE IMPORTANCE OF COGNITIVE THINKING IN THE MENTAL ACTIVITY OF SCHOOL STUDENTS (Universal International Scientific Journal, 2026)
The educational process organized on the basis of this article approach requires conscious and reasoned thinking. As a result of a complex and content-rich cognitive load, the effectiveness of thinking activity increases significantly. Cognitive research in the field of education is primarily aimed at identifying and developing the intellectual characteristics of the student's personality. In particular, they include: posing various problems and being able to solve them; responding flexibly and quickly to changing situations; putting forward assumptions and testing them; consciously mastering the environment; clearly imagining the system of the subject being studied; forming intellectual competence and skills; acting correctly in changing conditions, etc. Based on these characteristics, it can be said that cognitive educational technologies provide active participation of cognitive activity in the process of receiving and processing external information, regardless of its source. They involve the effective use of advanced pedagogical methods and tools based on the theories of cognitive psychology. In addition, such technologies not only support the continuous professional growth of teachers, but also accelerate the learning process, increase student engagement in education, and harmonize cooperation between teachers and students.
Keywords: Cognitive competencies; Competence; Cognitive activity